2013
DOI: 10.1002/ajh.23537
|View full text |Cite
|
Sign up to set email alerts
|

Novel G377S (c.1246G>T) mutation associated with Gaucher disease type 1

Abstract: To the editor: My father, Kenneth M. Moser, MD, was a pioneer in pulmonary medicine. His passion and best known work was in pulmonary vascular diseases, but he also underlined the importance of invasive diagnostics in approaching acute diffuse pulmonary infiltrates [1]. After spending decades hearing about his efforts to save the lives of those suffering from pulmonary diseases, it never occurred to me that I would almost die from a serious respiratory illness.Diagnosed with myelofibrosis in 2009, my body has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…[10] In our present study, we reviewed the new mutations reported from 2008 to 2018 (Table 1). [2,7,9–21] As shown in Table 1, more mutations were identified in type 1 GD than type 2 and 3 GD in recent years. The mutation spectrum of GBA in Chinese patients was quite different from those seen in Jewish and non-Jewish Caucasian patients.…”
Section: Discussionmentioning
confidence: 99%
“…[10] In our present study, we reviewed the new mutations reported from 2008 to 2018 (Table 1). [2,7,9–21] As shown in Table 1, more mutations were identified in type 1 GD than type 2 and 3 GD in recent years. The mutation spectrum of GBA in Chinese patients was quite different from those seen in Jewish and non-Jewish Caucasian patients.…”
Section: Discussionmentioning
confidence: 99%
“…A substitution of glycine for serine in the same codon (p.Gly377Ser) was previously described in patients with GD-1 and GD-2 of Portuguese and Spanish ancestry. [9][10][11] The p.Gly377Cys results in a disruptive amino acid substitution from a small and nonpolar amino acid (glycine, Gly) to a sulfur-containing amino acid (cysteine, Cys). This results in lower GCase enzymatic activity in comparison with other mutants (Figure 1), predicting an earlier onset and rapidly progressive clinical course as observed in the twins reported here.…”
Section: Discussionmentioning
confidence: 99%